Occurrence of Strongyloides stercoralis in rural areas adjacent to Dhaka city (Bangladesh Journal of Zoology, 2021)
The present study was designed to investigate Strongyloides stercoralis infection in rural communities of Savar and Gazipur. A total of 160 stool samples were collected from the inhabitants of the study areas during December 2016 to November 2017. The samples were processed by direct smear, formol-ether concentration technique and Harada-Mori culture. The overall prevalence of S. stercoralis was 10.63%; 11% in Savar and 10% in Gazipur. The elderly people were more prone to S. stercoralis infection. No respondent belonging to age group of 11-20 years was found positive for infection. Poor educational status, inferior financial condition and inadequate hygiene practice were found as potential risk factors (P